Radical Prostatectomy: Sequelae in the Course of Time - Kesch, Claudia; Heidegger, Isabel; Kasivisvanathan, Veeru; Kretschmer, Alexander; Marra, Giancarlo; Preisser, Felix; Tilki, Derya; Tsaur, Igor; Valerio, Massimo; van den Bergh, Roderick C. N.; Fankhauser, Christian D.; Zattoni, Fabio; et al. (Frontiers in Surgery, 2021)
Objective: Radical prostatectomy (RP) is a frequent treatment for men suffering from localised prostate cancer (PCa). Whilst offering a high chance for cure, it does not come without a significant impact on health-related quality of life. Herein we review the common adverse effects RP may have over the course of time. Methods: A collaborative narrative review was performed with the identification of the principal studies on the topic. The search was executed by a relevant term search on PubMed from 2010 to February 2021. Results: Rates of major complications in patients undergoing RP are generally low. The main adverse effects are erectile dysfunction varying from 11%-87% and urinary incontinence varying from 0%-87% with a peak in functional decline shortly after surgery, and dependen on definitions. Different Less frequent side effects also need to be taken into account. The highest rate of recovery is seen within the first year after RP, but even long-term improvements are possible. Nevertheless, for some men these adverse effects are long lasting and different, less frequent side effects also need to be taken into account. Despite many technical advances over the last two decades no surgical approach can be favoured when looking at long-term outcome, as surgical volume and experience as well as individual patient characteristics are still the most influential variables. Conclusions: The frequency of erectile function and urinary continence side effects after RP, and the trajectory of recovery, need to be taken into account when counseling patients about their treatment options for prostate cancer.